Silicon Oxide‐Rich Diamond‐Like Carbon: A Conformal, Ultrasmooth Thin Film Material with High Thermo‐Oxidative Stability. Issue 2 (28th November 2018) - Mangolini, Filippo; McClimon, J. Brandon; Segersten, Justin; Hilbert, James; Heaney, Patrick; Lukes, Jennifer R.; Carpick, Robert W.
Abstract: Silicon oxide‐containing diamond‐like carbon (a‐C:H:Si:O) films are a promising class of protective coatings for environmentally‐demanding applications owing to their lower residual stresses and superior thermal stability and oxidation resistance relative to undoped diamond‐like carbon. However, existing versions of a‐C:H:Si:O deposited by traditional methods such as plasma‐enhanced chemical vapor deposition (PECVD) undergo substantial degradation and oxidation at temperatures above 250 °C. This, together with the difficulty of PECVD in depositing conformal coatings on complex geometries such as high‐aspect‐ratio features, has limited the applicability of a‐C:H:Si:O. Here, the unique capabilities of plasma immersion ion implantation and deposition (PIIID) to grow silicon oxide‐rich diamond‐like carbon materials that are ultrasmooth, continuous, and conformal on high‐aspect‐ratio topographies are explored. The high concentration of silicon and oxygen in PIIID‐grown films (23 ± 5 at.% and 11 ± 4 at.%, respectively) is unrivalled for this class of materials, and drastically increases the resistance to oxidation at high temperatures, compared with PECVD‐grown films. The results open the path for using a‐C:H:Si:O in applications involving exposure of materials to extreme environments. Abstract : A new variant of silicon‐ and oxygen‐containing amorphous carbon with high thermal stability and an ultraflat morphology is produced and characterized. The film possesses a roughness below 0.2 nm across large areas and shows the ability to retain a highly sp 3 ‐hybridized structure with a significant reservoir of carbon in the near‐surface region even after extended aerobic annealing at 450 °C.